2000
DOI: 10.1007/bf02258292
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind crossover study of sacral nerve stimulation for fecal incontinence

Abstract: There is a marked, unequivocal improvement in symptoms of fecal incontinence with sacral nerve stimulation shown in this double-blind crossover trial. Sacral nerve stimulation improves the quality of life in selected patients with fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 13 publications
1
115
0
3
Order By: Relevance
“…This finding agrees with a previous similar study in patients treated with SNS for incontinence. 14 However, the numbers were small, due to limited numbers of patients who have clinical benefit at sub-sensory stimulation levels. Further larger studies would be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with a previous similar study in patients treated with SNS for incontinence. 14 However, the numbers were small, due to limited numbers of patients who have clinical benefit at sub-sensory stimulation levels. Further larger studies would be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Yet symptom improvement can also be seen in patients who didn't have a sensory response upon implantation which suggests that the amplitude can be set at a level below the sensory threshold without affecting the outcome. [18][19][20] This reflects the suggestion that the median amplitude necessary to provoke a sensory response is lower in patients with greatest reduction of symptoms. [21] 3.5 Thinking outside the box Building on the general principal of neuromodulation through sacral nerve stimulation and supported by cases similar to ours, other techniques have been developed where peripheral nerves are stimulated who connect anatomically to sacral nerves.…”
Section: Amplitudementioning
confidence: 52%
“…Several retrospective trials and 3 prospective crossover trials have proven the beneficial effect of this technique in the treatment of faecal incontinence with an overall success rate of 65%-80% among these patients. [1][2][3] The main advantage of this new technique is the possibility of reliably testing its effectiveness before carrying out the definitive procedure. [4] In this article, a case is described of a 74-year-old patient who had a sacral lead implanted in 2002 in another hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The first sacral neuromodulation application was performed by Feler et al (6) in 1981, with indications of urinary incontinence, urinary frequency, and non-obstructive urinary retention. In addition, similar studies have been conducted for fecal incontinence (7,8). As a result of the abovementioned studies, for patients with insufficient responses to other treatments, FDA approval in the USA was obtained for the management of urinary incontinence in 1997, the approval for the treatment of polyuria and urinary retention not caused by an obstruction was obtained in 2006, and the approval for fecal incontinence was obtained in 2011.…”
Section: Historymentioning
confidence: 97%